2015
DOI: 10.1051/0004-6361/201527180
|View full text |Cite
|
Sign up to set email alerts
|

VLT/MUSE discovers a jet from the evolved B[e] star MWC 137

Abstract: Aims. Not all stars exhibiting the optical spectral characteristics of B [e] stars are in the same evolutionary stage. The Galactic B[e] star MWC 137 is a prime example of an object with uncertain classification, where previous work has suggested either a pre-or a postmain sequence classification. Our goal is to settle this debate and provide a reliable evolutionary classification. Methods. Integral field spectrograph observations with the Very Large Telescope Multi Unit Spectroscopic Explorer (VLT MUSE) of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 86 publications
6
41
0
Order By: Relevance
“…MWC 137 is embedded into a rich CSE . Although its nature has been debated, observations favor a post-main sequence scenario (Mehner et al 2016), especially with the detection of both 12 CO and 13 CO emission features Muratore et al 2015). In Fig.…”
Section: Mwc 137mentioning
confidence: 96%
See 2 more Smart Citations
“…MWC 137 is embedded into a rich CSE . Although its nature has been debated, observations favor a post-main sequence scenario (Mehner et al 2016), especially with the detection of both 12 CO and 13 CO emission features Muratore et al 2015). In Fig.…”
Section: Mwc 137mentioning
confidence: 96%
“…As these velocities are smaller than that of the CO ring, their corresponding rings are located further away from the CO ring (with no other emitting region closer to the star). Using a stellar mass estimate of 10-15 M ⊙ (Mehner et al 2016) we can calculate the ring radii for the CO and the four [OI] rings (see Table 3).…”
Section: Mwc 137mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, our findings of possible multiple rings centered at various velocities is in agreement with what was reported for other B[e] stars in binary systems (see, e.g., Maravelias et al 2018). Alternatively, the blue wings of the [N II] and [Ni II] lines might suggest high-velocity outflows of ionized gas, maybe in the form of a jet or knots, as is seen in the B[e] star MWC 137 (Mehner et al 2016;Kraus et al 2017).…”
Section: Kinematics Of the Circumstellar Gasmentioning
confidence: 99%
“…We do not have evidence of a dense disk in our data (although Schulte-Ladbeck et al 1993 andDavies et al 2005 suggested the presence of a disk at a few stellar radii), but we also do know that RMC 127 is a fast rotator (with a projected rotational velocity of 105 km s 1 -; Agliozzo et al 2017b). A collimated outflow was discovered from the evolved B[e] star MWC 137 (Mehner et al 2016).…”
Section: Livio 2000)mentioning
confidence: 99%